Isolation and Molecular Characterisation of Vibrio Vulnificus and Vibrio Parahaemolyticus from Cockles (Anadara Granosa) in Malaysia - Hussein, Nasreldin Elhadi (1999)
Antibiotic susceptibility, plasmid profiles and random amplification of polymorphic DNA were used to study strains of Vibrio vulnificus and Vibrio parahaemolyticus isolated from cockles (Anadara granosa). 36 strains of V vuln(ficus isolates were examined. The prevalent biotype was biotype 1 (72.2% of the isolates) and 2 (27.8%). Twenty one strains of biotypes 1 and 2 harboured plasmid DNA ranging in size from 1.4 to 9.7 megaDalton. No particular plasmid profile was predictive of a particular pattern of antibiotic susceptibility. Two primers demonstrated polymorphisms in all strains tested, producing bands ranging from 0.25 to 2.7 kb, indicating a high variability among both biotypes 1 and 2 of the V vulnificus strains investigated. RAPD identity across biotypes was also observed among the V vulnificus strains. 35 Vibrio parahaemolyticus Kanagawa-negative strains were isolated.· Twenty six strains of V parahaemolyticus were carried small plasmid(s) of 1.3 to 9.7 MegaDalton that enabled the V. parahaemolyticus to be grouped into eight plasmid patterns. The RAPD fingerprinting using three primers demonstrated polymorphisms in all thirty-five strains of V. parahaemolyticus tested, producing bands ranging from 0.25 to 3.9 kb. The RAPD profiles revealed a high level of DNA sequence diversity within the V. parahaemolyticus strains tested, and that cockles in the study area are populated by genetically polymorphic strains of V. parahaemolyticus.